Nutritional and Phenolic Antioxidant Properties of Pakistani Wheat Varieties as Influenced by Planting Period and Variety - Muhammad Nadeem; Muhammad Mushtaq; Muhamad Farhan Jahangir Chughtai; Adnan Khaliq; Muhammad Imran; Tanweer Aslam Gondal; Mohammad Ali Shariati; Anton Nesterenko; Dmitriy Kulikov (AGRIVITA, Journal of Agricultural Science, 2021)
The objective of this study was to investigate the effects of variety and plant environment on nutritional composition, phenolic contents and antioxidant activities from commercial wheat cultivars grown in Pakistan. Chemical composition, total phenolic contents and antioxidant activities were measured in twenty-seven spring wheat varieties grown for two cropping years. Preliminary assessment of antioxidant strength of the extracts was carried out by the evaluation of total phenolic contents (TPC), antioxidant activity (AA) and free radical scavenging activity (FRSA). The grain length, width and a thousand kernel weight of different wheat varieties ranged from 6.75-6.77 mm, 3.44-3.45 mm and 42.95-45.16 g respectively. Similarly, the moisture, ash, crude fat, crude fiber, crude protein, wet gluten, dry gluten, flour gliadins, flour glutenins contents and SDS-sedimentation value varied from 10.23-10.61%, 1.47-1.48%, 1.16-1.21%, 1.37-1.40%, 11.86-12.02%, 25.39-25.46%, 8.85-8.87%, 0.46-0.52%, 0.46-0.49% and 24.99-25.85 ml respectively among different wheat varieties. In the same way, the results for total phenolic contents, free radical scavenging activity (DPPH assay) and antioxidant activity via beta carotene bleaching assay varied from 12.40-11.73 mg GE/g, 18.48-18.99% and 14.23-15.97% respectively. Our research clearly indicated that wheat variety, input conditions, environmental and genotypic variations gave effects on the phenolic antioxidant properties.